Plankton Distribution Analysis with Underwater Acoustic Remote Sensing - A Abdullah; Pratomo D.G.; Khomsin (BIO Web of Conferences)
Hydroacoustic methods are rapidly growing as a key technique in marine ecology, particularly for efficient and non-invasive monitoring of plankton and fish. This technology utilises sound waves to detect, measure and map the distribution of marine biota by analysing the backscatter strength (Sv). This study used a SIMRAD EK-60 echosounder and a Seabird SBE37 CTD to analyse the relationship between plankton distribution and environmental parameters, such as temperature, salinity and conductivity. Results show that plankton are more abundant in the surface layer with high temperature and low to moderate salinity, while conditions at depth limit their biological activity. This research contributes to the sustainable management of marine resources through an integrated hydroacoustic approach.